Clinical efficacy and mechanism of the combination of autologous platelet-rich gel and recombinant human acidic fibroblast growth factor in the management of refractory diabetic foot - Sheng, Xia; Hu, Ling; Li, Ting; Zou, Yi; Fu, Hai-Yan; Xiong, Guo-Ping; Zhu, Yan; Deng, Bo; Xiong, Lei-Lei; Yin, Xiao-Ling (Frontiers in Endocrinology, 2024)
Objective: This study aims to explore the influence of combining autologous platelet-rich gel (APG) with continuous vacuum-sealed drainage (CVSD) and the exogenous recombinant human acidic fibroblast growth factor (rh-aFGF) on the healing processes of diabetic foot ulcers (DFU). The primary objective is to elucidate the complex molecular mechanisms associated with DFU, providing innovative perspectives for its treatment. Methods: Ninety patients diagnosed with DFU were randomly allocated into three distinct groups. Group A underwent CVSD following wound cleansing to facilitate healing. In Group B, in addition to conventional treatment, negative pressure wound therapy was applied, and rh-aFGF was introduced into normal saline for lavage, building upon the procedures of Group A. Group C received APG along with the interventions applied in Group B. The clinical efficacy of each group was systematically observed and analyzed. Additionally, changes in plasma oxidative stress, inflammatory markers, vascular endothelial growth factor (VEGF), and pigment epithelium-derived factor (PEDF) were assessed both before treatment and 14 days post-treatment. Results: Following treatment, all groups exhibited commendable clinical efficacy. Group C demonstrated a superior wound healing rate, reduced frequency of dressing changes, and shorter wound healing duration (P < 0.05). Compared to baseline measurements, the levels of superoxide dismutase and PEDF increased, while malondialdehyde, VEGF, interleukin-6, interleukin-8, and monocyte chemotactic factor MCP-1 decreased in the wound tissue across all groups. Notably, Group C showed the most significant improvement in clinical efficacy and fortification of molecular mechanisms against oxidative stress (all P < 0.05). Conclusions: The integrative therapeutic approach combining APG with CVSD and rh-aFGF demonstrates notable efficacy in advancing wound healing. This effectiveness is evident through the reduced frequency of dressing changes and alleviation of wound-related pain. Additionally, the treatment regimen improves the cure rate for challenging, refractory wounds. These favorable outcomes can be attributed to the reduction of oxidative stress levels, attenuation of the local inflammatory response, and the enhancement of the balance between PEDF and VEGF.